2017
DOI: 10.1038/s41598-017-07608-8
|View full text |Cite
|
Sign up to set email alerts
|

Neural substrates of embodied natural beauty and social endowed beauty: An fMRI study

Abstract: What are the neural mechanisms underlying beauty based on objective parameters and beauty based on subjective social construction? This study scanned participants with fMRI while they performed aesthetic judgments on concrete pictographs and abstract oracle bone scripts. Behavioral results showed both pictographs and oracle bone scripts were judged to be more beautiful when they referred to beautiful objects and positive social meanings, respectively. Imaging results revealed regions associated with perceptual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 59 publications
3
45
1
Order By: Relevance
“…Taken together, the involvement of these brain regions supported our hypothesis that the perception and appreciation of landscape gardens may rely on the common neural areas that are active in the perception and appreciation of other visual stimuli, including the combined participation of visual perceptual processing, cognitive processing, and rewarding emotional experience (Berlyne, ; Cupchik, ; Wang, Mo, Mo, et al, ; Zhang et al, ; Zhang, Lai, He, Zhao, & Lai, ); this finding may support the framework of experiencing art to the neuroscience underlying our perception and appreciation of architecture (Shimamura, ), suggesting that the perception and appreciation of architecture engage the sensorimotor, knowledge‐meaning, and emotion‐valuation systems (Chatterjee, ; Coburn et al, ).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Taken together, the involvement of these brain regions supported our hypothesis that the perception and appreciation of landscape gardens may rely on the common neural areas that are active in the perception and appreciation of other visual stimuli, including the combined participation of visual perceptual processing, cognitive processing, and rewarding emotional experience (Berlyne, ; Cupchik, ; Wang, Mo, Mo, et al, ; Zhang et al, ; Zhang, Lai, He, Zhao, & Lai, ); this finding may support the framework of experiencing art to the neuroscience underlying our perception and appreciation of architecture (Shimamura, ), suggesting that the perception and appreciation of architecture engage the sensorimotor, knowledge‐meaning, and emotion‐valuation systems (Chatterjee, ; Coburn et al, ).…”
Section: Discussionsupporting
confidence: 67%
“…It is noteworthy that the perception and appreciation of landscape gardens also engaged the right cuneus and hippocampus; past studies have shown that the cuneus is responsive to the appreciation of representational materials (Mizokami et al, ), and the activity of the hippocampus correlates with the consolidation of a tendency toward a preference into a firm decision (Ito et al, ). These cortical regions imply that the specific activations for appreciating landscape gardens may be linked to multiple layers of processing, including the perception of the global configuration and layout of architecture, the recognition of the architectural style and motif, the rewarding emotional experience, and the embodied motivation to approach the structure (Vartanian et al, ; Zhang et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 clearly demonstrates the flow of information through different circuits, a very similar process to the flow of signals in the brain. The internal structure of this model is supported by the research conclusion that aesthetic appreciation and judgement requires a distributed neural network of activation in the brain, rather than in a single neural region [ 5 , 22 , 24 , 37 ]. The neural underpinnings for the information-processing model at least cover three functionally distinct sets of brain regions.…”
Section: Models Of Aesthetic Appreciationmentioning
confidence: 94%
“…In this vein, Zhang et al ( 2017 ) recently used fMRI to explore the dispute between objectivist and subjectivist philosophies of beauty: Is beauty a quality of objects or a quality we attribute to objects? They asked participants to judge unfamiliar ancient Chinese characters as beautiful or ugly.…”
mentioning
confidence: 99%
“…Zhang et al ( 2017 ) found widespread brain activity common to judgments of both sorts of characters, but they also found activity in certain brain regions specific either to judging the beauty of pictographs or judging the beauty of ideographs. They saw in these specific patterns the neural signatures of two distinct kinds of beauty, one related to object features and another to subjective processes.…”
mentioning
confidence: 99%